Retrospective study on occurrence of tick borne haemoparasitic diseases in dairy animals of eastern Haryana - BHANOT, VANDNA (The Indian Journal of Animal Sciences, 2021)
Tick borne haemoparasitic diseases (THBDs) account for substantial losses in terms of decreased working capacity, growth and productivity of cattle. The occurrence of TBHDs in dairy animals of eastern Haryana was studied by screening 3,200 blood samples during the period of July 2014 to June 2019. The examination of stained blood smears from pyretic cross bred cows (2,339) and buffaloes (861) revealed significantly higher infection in cows (50.5%) than buffaloes (0.6%). Among the haemoprotozoan diseases, the occurrence of theileriosis in pyretic dairy animals was found to be high (32.6%), followed by anaplasmosis (2.4%) and babesiosis (2.0%). TBHDs were found most prevalent in summers (42.4%), followed by rainy season (38.3%) and least in winters (27.5%). Low Hb and TEC levels and increase in TLC count was noted in TBHDs affected animal as compared to healthy group. Year-wise, among haemoparasitic infection, particularly Theileriosis was higher during 2014-15 followed by decline in 2015-16 and later revealed increasing percentage of haemoparasitic infection in dairy animals every year.